2014
DOI: 10.1088/1748-9326/9/8/085003
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the permafrost carbon feedback on global climate

Abstract: Degrading permafrost can alter ecosystems, damage infrastructure, and release enough carbon dioxide (CO 2 ) and methane (CH 4 ) to influence global climate. The permafrost carbon feedback (PCF) is the amplification of surface warming due to CO 2 and CH 4 emissions from thawing permafrost. An analysis of available estimates PCF strength and timing indicate 120 ± 85 Gt of carbon emissions from thawing permafrost by 2100. This is equivalent to 5.7 ± 4.0% of total anthropogenic emissions for the Intergovernmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
267
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 335 publications
(272 citation statements)
references
References 52 publications
4
267
1
Order By: Relevance
“…Several studies have proposed that DOC components are more labile than POC, as the DOC contributed from permafrost was possibly unprocessed before mobilization and consisted predominantly of labile low-molecular-weight and few aromatic compounds Waldrop et al, 2010). This degradation process most likely causes the formation of greenhouse gases (Schaefer et al, 2014;Schuur et al, 2015). Knoblauch et al (2013) showed that the highest OM mineralization rates and CO 2 production were found directly after permafrost thaw and projected a loss of initial OC of 15% within 100 years.…”
Section: Processes After Initial Slumpingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have proposed that DOC components are more labile than POC, as the DOC contributed from permafrost was possibly unprocessed before mobilization and consisted predominantly of labile low-molecular-weight and few aromatic compounds Waldrop et al, 2010). This degradation process most likely causes the formation of greenhouse gases (Schaefer et al, 2014;Schuur et al, 2015). Knoblauch et al (2013) showed that the highest OM mineralization rates and CO 2 production were found directly after permafrost thaw and projected a loss of initial OC of 15% within 100 years.…”
Section: Processes After Initial Slumpingmentioning
confidence: 99%
“…That leads to increased greenhouse gas emissions and, ultimately, climate warming -a process known as the permafrost carbon feedback. However, due to the complexity of environmental processes, the intensity of this feedback remains unclear (Schaefer et al, 2014;Schuur et al, 2015). Besides being released as greenhouse gases, OM can be redeposited on land or transported to aquatic systems where it can be further mineralized in the water column or buried in sediments (Cory et al, 2013;Letscher et al, 2011;Vonk et al, 2014;Woods et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Yedoma deposits formed during the late Pleistocene cold stages in unglaciated Beringia and are characterized by high ice contents, fine grain size, and a good preservation of organic carbon . As the terrestrial Arctic warms up, permafrost soils, including those located in IWPs in drained lake basins, are expected to release substantial greenhouse gas emissions that will generate a positive feedback to global warming (Dutta et al, 2006;Koven et al, 2011;Schaefer et al, 2014). Walter Anthony et al (2014) indicated that widespread permafrost thaw could ultimately result in reduced lake and wetland abundance caused by drainage and drying, facilitating rapid decomposition of freeze-locked organic matter.…”
Section: Introductionmentioning
confidence: 99%
“…This will have a wide variety of ecosystem effects (Alexander and Mack, 2016): in particular, rising temperatures and increasing fire will likely result in changes in soil temperature and permafrost degradation (Pastick et al, 2015;Zhang et al, 2015;Genet et al, 2013;Helbig et al, 2016), with subsequent hydrology changes that will influence soil greenhouse gas (GHG) fluxes to the atmosphere (Schädel et al, 2014). Such fluxes are a large component of the global C cycle and could result in a significant and positive climate feedback Koven et al, 2011;Schaefer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%